Pengaruh Bauran Pemasaran Jasa terhadap Kepuasan dan Loyalitas Nasabah pada PT Pegadaian (Persero) Cabang Mengwi Badung - Letrio Putra, I Gede Nyoman Ade; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 2 No 8 (2013), 2013)
This study was conducted in order to know the influence of marketing mix consists of product, price, promotion, place, people, physical evidence, and process satisfaction and customer loyalty at PT. Pegadaian Cabang Mengwi, Badung, Bali. 100 customers were sampled in the study by distributing questionnaires as data collection techniques. Path analysis as an analytical technique used in this study. Discovery gives results that there is significant influence of the marketing mix consisting of product, price, promotion, place, people, physical evidence, and process simultaneously and partially on customer satisfaction and loyalty at PT. Pegadaian Cabang Mengwi, Badung. Keywords : marketing mix of services, customer satisfaction, and customer loyalty